Finite element modeling of polycristalline solids - Dawson, Paul; Beaudoin, Armand; Mathur, Kapil; Sarma, Gorti (European Journal of Computational Mechanics, 1994)
Anisotropy in the plastic flow of polycristalline solids can be computed based on the slip characteristics of individual crystals and included in finite element formulations as the constitutive description of the material. A variety of approaches exist for merging finite element formulations and polycrystal plasticity, and depending on the intended application the two may have different relationships to each other. We summarize two regimes that we refer to as large and small scale applications and outline a finite element formulation for each. Examples of both large and small scale applications are presented and some important issues associated with the implementation of each are discussed.